2020
DOI: 10.1002/asi.24440
|View full text |Cite
|
Sign up to set email alerts
|

On the causal relation between real world activities and emotional expressions of social media users

Abstract: Social interactions through online social media have become a daily routine of many, and the number of those whose real world (offline) and online lives have become intertwined is continuously growing. As such, the interplay of individuals' online and offline activities has been the subject of numerous research studies, the majority of which explored the impact of people's online actions on their offline activities. The opposite direction of impact—the effect of real‐world activities on online actions—has also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Second, this study identified the impact of emotional valence on information sharing during public health crises. As suggested by ELM, audiences pay attention to emotional cues in a message (Petty & Cacioppo, 1986 ), especially for online discussions (Falavarjani et al, 2021 ). Our results show that different emotions may exert varying effects on social media information sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study identified the impact of emotional valence on information sharing during public health crises. As suggested by ELM, audiences pay attention to emotional cues in a message (Petty & Cacioppo, 1986 ), especially for online discussions (Falavarjani et al, 2021 ). Our results show that different emotions may exert varying effects on social media information sharing.…”
Section: Discussionmentioning
confidence: 99%
“…The user features may have different effects on users' behavior and information dissemination on the social media platform (Falavarjani et al ., 2021). The user features selected in this study include the number of accounts followed by a user, number of followers, user category, user activity and initial topic attentiveness.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of online reviews, Volume it , was calculated as the number of doctor i's online reviews generated by their patients in the period t. As previously mentioned, we used review length to measure review effort. To construct the measures of review length and emotional expression, we used Linguistic Inquiry and Word Count (LIWC), which is a well-validated text analytics tool widely used in prior research (e.g., Cohan et al, 2017;Falavarjani et al, 2021;Huang et al, 2017). LIWC can accurately identify emotion in written language and capture people's social and psychological state (Tausczik & Pennebaker, 2010).…”
Section: Variable Operationalizationmentioning
confidence: 99%